Growth of the Greater Indian Landmass and its assembly in Rodinia: Geochronological evidence from the Central Indian Tectonic Zone - Bhowmik, S.; Wilde, Simon; Bhandari, A.; Pal, T.; Pant, N. (Elsevier Science BV, 2012)
The Sausar Mobile Belt at the southern margin of the Central Indian Tectonic Zone (CITZ) is a key unit in constraining the timing of continent–continent collision between the North and South Indian cratonic blocks. It consists of three domains – northern, central and southern – that record the history of this collision. Rocks from the northern and central domains were metamorphosed under medium pressure–medium temperature conditions and define a clockwise P–T trajectory. Monazite spot ages in garnet–cordierite migmatite from the western extremity of the northern domain yield a weighted mean age of 1043±18 Ma (MSWD=0.26) for monazite cores and 955±11Ma (MSWD=0.43) for monazite rims. These ages are correlated with peak granulite facies metamorphism and post-peak decompression, respectively. Garnet–orthoamphibole gneiss and garnet–cordierite migmatite from the central and eastern sectors of the northern domain, respectively, yield weighted mean ages (for monazite) of 974±9 Ma (MSWD=0.53) and 989±9 Ma (MSWD=1.3). These ages mark the timing of retrograde metamorphism in the northern domain. Charnockite in the northern domain, which was emplaced during post-peak decompression, records a SHRIMP U–Pb zircon concordia age of 938±3 Ma (MSWD=1.9).Lu–Hf isotopic analyses of these zircons show a restricted range of εHf(T) values (from -2.9 to -5.8 with a mean of -4.3) and have TDMc model ages from 1995 to 2163 Ma (with a mean of 2064 Ma), implying derivation of charnockitic magma from a Paleoproterozoic crustal source. In contrast, garnet–staurolite–kyanite schist and garnet–biotite–muscovite–quartz schist from the central domain of the Sausar Mobile Belt yield weighted mean monazite ages of 1062±13 Ma (MSWD=1.2) and 993±19 Ma (MSWD=0.16), respectively, which are broadly correlated with the peak and retrograde stages of metamorphism from this domain. Geochronological data thus tightly bracket the collisional orogeny in the CITZ at between 1.06 Ga and 0.94 Ga.When combined with recent data from collisional belts further east of the CITZ, namely the Chhotanagpur Gneissic Complex and Shillong Plateau Gneissic Complex, a uniformity of Mesoproterozoic to Early Neoproterozoic events is evident, implying final amalgamation of the North and South Indian blocks at this time along a ~1500 km long orogenic belt. This means that two or more separate blocks were in existence at the time of incorporation within Rodinia, not a single block as suggested in most current models.